Reformulasi Kebijaksanaan Perberasan Nasional - Faisal Kasryno; Pantjar Simatupang; Effendi Pasandaran; Sri Adiningsih (Forum penelitian Agro Ekonomi, 2001)
EnglishRapid rice production growth leading to the achievement of rice self sufficiency in 1984 came from productivity and harvested area which both had been growing rapidly as the results of technological break through (the Green Revolution), infrastructure development, rice field extensification and comprehensive incentive as well as facilitating policies. It was a phenomenal achievement. The rice self sufficiency was proven not sustainable, however. This review shows that since mid 1980's rice production growth has been slowing down and increasingly unstable value to innovation stagnation, over intensification syndrome, over extensification and land conversion, declining incentives and institutional fatigue. Indonesia has become rice net importer since early 1990's and even the largest world rice importer since late 1990's that undermines national food security. Revitalization of trend rice sector has become an imperative strategic national policy agenda. The paper also discusses some policy options for revitalizing the rice sector. IndonesianPesatnya pertumbuhan produksi beras yang memungkinkan Indonesia meraih swasembada beras pada tahun 1984 berasal dari pertumbuhan produktivitas dan luas panen sebagai hasil dari terobosan teknologi (Revolusi Hijau), pembangunan infrastruktur, perluasan areal, dan kebijakan insentif maupun fasiltasi yang komprehensif. Keberhasilan tersebut sungguh fenomenal. Namun demikian, swasembada berat tersebut terbukti tidak berkelanjutan. Ulasan ini menunjukkan bahwa sejak pertengahan tahun 1980'an pertumbuhan produksi beras telah mengalami perlambatan dan semakin tidak stabil pula sebagai akibat dari stagnasi inovasi, sindrome over intensifikasi, over ekstensifikasi dan konversi lahan, penurunan insentif dan kelesuan institusional. Indonesia telah menjadi importif netto beras sejak awal tahun 1990-an dan bahkan menjadi importif terbesar di dunia sejak akhir tahun 1990'an sehingga ketahanan pangan nasional semakin rawan. Revitalisasi sektor perberasan nasional merupakan salah satu agenda kebijakan strategis mendesak. Makalah ini juga membahas beberapa opsi kebijakan dalam rangka revitalisasi sektor perberasan nasional.